2008
DOI: 10.1111/j.1468-0432.2007.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

What Would You Sacrifice? Access to Top Management and the Work–life Balance

Abstract: This article is based on a current research, combining quantitative (human resources figures and statistics) and qualitative data (60 interviews with career managers, top managers and high potential talents, both men and women), conducted in a major French utility company on the subject of diversity and more specifically on the issue of women's access to top management positions. The main purpose of this research is to understand the difficulties women may encounter in the course of their occupational career l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
150
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(172 citation statements)
references
References 25 publications
5
150
0
14
Order By: Relevance
“…Linehan (2000) says in her study of 50 senior international female managers that the majority of the married women in the study believed that progressing to the top of their managerial careers had been facilitated by the careers of their spouses being placed secondary to their own careers. Guillaume and Pochic (2009) also conclude that to have access to top management it is implicitly expected that the spouse has sacrificed his/her career. They add that it is most commonly the woman's sacrifice: the woman is generally expected to sacrifice her career for the sake of her spouse.…”
Section: From 2000 Onwardsmentioning
confidence: 95%
See 1 more Smart Citation
“…Linehan (2000) says in her study of 50 senior international female managers that the majority of the married women in the study believed that progressing to the top of their managerial careers had been facilitated by the careers of their spouses being placed secondary to their own careers. Guillaume and Pochic (2009) also conclude that to have access to top management it is implicitly expected that the spouse has sacrificed his/her career. They add that it is most commonly the woman's sacrifice: the woman is generally expected to sacrifice her career for the sake of her spouse.…”
Section: From 2000 Onwardsmentioning
confidence: 95%
“…The significance of the subordination of one spouse's career to the managerial career of the other spouse is a result found in recent studies about advancing to top management (Linehan, 2000;Guillaume & Pochic, 2009). Linehan (2000) says in her study of 50 senior international female managers that the majority of the married women in the study believed that progressing to the top of their managerial careers had been facilitated by the careers of their spouses being placed secondary to their own careers.…”
Section: From 2000 Onwardsmentioning
confidence: 97%
“…Of course, this leaves open the question of the nature of career anchors, and in particular their stability. Research has shown that women make adaptations to their career goals (e.g., Guillaume and Pochic, 2009) and it is debatable whether career anchors, though socially-grounded, are stable after the very early career years, or whether they may change according to later work experiences. This amounts to the question of whether women's "choices" indeed really are choices or just rationalized constraints (e.g., Crompton and Lyonette, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, further insight is needed to understand how employees in the three generations (Millennials/Gen Y, Gen X, and Baby Boomers), which predominantly comprise the current workplace, view organizational leadership in relationship to work-life balance. Since the voices of women have been studied extensively (Eagly & Carli, 2007;Favero & Heath, 2012;Guillaume & Pochic, 2009;Jyothi & Jyothi, 2012;Roebuck, Smith, & Elhaddaoui, 2013;Schueller-Weidekamm & Kautzky-Willer, 2012), this exploratory study examines the perspectives of working men by asking how different generations of men view organizational leadership in light of work-life balance. The researchers used a convenience sample to invite men to participate in an online survey about organizational leadership, work-life balance and generational factors.…”
mentioning
confidence: 99%